Pengaruh Glass Ceiling Terhadap Kepemimpinan Strategis Wanita Dalam Bidang Militer Di Indonesia - Aflah, Muhammad Naufal; Mawaddah, Laili Rahmah (Jurnal Kajian Stratejik Ketahanan Nasional, 2021)
In developing a career in the military field, there is no difference in opportunities and opportunities between male and female soldiers. However, until now there is still a phenomenon that shows that the number of women who occupy structural positions is very small. If any, the total does not have a representative composition in terms of gender. The existence of an obstacle that only applies to women, makes it difficult for women to reach the top of careers in their fields and leadership positions. As a result, there are only a few women who become leaders, especially leaders in the military world. Barriers that prevent women from occupying the peak of their careers or leadership positions, but do not occur in men are called the glass ceiling. This study aims to analyze whether there are still many women who are hindered by the existence of obstacles in their careers (glass ceiling) in the military field and to find out the empowerment and success of female soldiers in fighting the glass ceiling within the military scope to achieve structural or functional positions in opportunities, roles, and opportunities. and career prospects, including combat roles. The type of research applied is descriptive analytical. Data collection techniques obtained through literature study. The data analysis method applied in this research is the qualitative analysis method. The results of the study show that so far there have been no female military soldiers who have succeeded in occupying strategic positions. However, there are many female soldiers who have managed to reach the highest positions according to their scientific fields. The female soldiers are usually formed from staff ranks or from several fields according to their background or expertise such as military health, military law, military administration, and military finance. Therefore, an organization or institution should provide trust and opportunities and support women so that they can play a leadership role. Keywords: Glass Ceiling; Leadership; Woman; Strategic Position; Military